Volatile anesthetics and the treatment of severe bronchospasm: a concept of targeted delivery. (2015) - Mondoñedo, Jarred R.; McNeil, John S.; Amin, Samir D.; Herrmann, Jacob; Simon, Brett A.; Kaczka, David W.
Abstract : Status asthmaticus (SA) is a severe, refractory form of asthma that can result in rapid respiratory deterioration and death. Treatment of SA with inhaled anesthetics is a potentially life-saving therapy, but remarkably few data are available about its mechanism of action or optimal administration. In this paper, we will review the clinical use of inhaled anesthetics for treatment of SA, the potential mechanisms by which they dilate constricted airways, and the side effects associated with their administration. We will also introduce the concept of 'targeted' delivery of these agents to the conducting airways, a process which may maximize their therapeutic effects while minimizing associated systemic side effects. Such a delivery regimen has the potential to define a rapidly translatable treatment paradigm for this life-threatening disorder.